Process of permanent training of the higher education professional in the Ecuadorian context - Kléver Hernán García Gallegos; Silvia Maribel Sarmiento Berrezueta; María Julia Rodríguez (Centro Provincial de Información de Ciencias Médicas, 2016)
In the last years significant changes have happened for the sake of looking for the quality in the Ecuatorian system of higher education. To such effects some aspects related to the topic are analyzed, taking into account that mistakes still exist between the process of professors permanent training and the evaluation as agent of the occupational training.